2006
DOI: 10.1242/dev.02362
|View full text |Cite
|
Sign up to set email alerts
|

Conserved roles for Oct4 homologues in maintaining multipotency during early vertebrate development

Abstract: All vertebrate embryos have multipotent cells until gastrulation but, to date, derivation of embryonic stem (ES) cell lines has been achieved only for mouse and primates. ES cells are derived from mammalian inner cell mass (ICM) tissue that express the Class V POU domain (PouV) protein Oct4. Loss of Oct4 in mice results in a failure to maintain ICM and consequently an inability to derive ES cells. Here, we show that Oct4 homologues also function in early amphibian development where they act as suppressors of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
223
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 152 publications
(257 citation statements)
references
References 48 publications
(53 reference statements)
21
223
0
Order By: Relevance
“…The former aimed at maintaining the pluripotent state while the latter promotes gastrulation. The opposed and mutually repressive roles of the Oct3/ 4 and Cdx factors have been previously described in early mouse embryos, embryonic stem cells, and early tailbud frog embryos (Niwa et al, 2005;Morrison and Brickman, 2006). Our results show that this same regulatory module, i.e., the negative cross-regulation between Oct3/4 and Cdx, is employed to regulate the transition into gastrulation.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The former aimed at maintaining the pluripotent state while the latter promotes gastrulation. The opposed and mutually repressive roles of the Oct3/ 4 and Cdx factors have been previously described in early mouse embryos, embryonic stem cells, and early tailbud frog embryos (Niwa et al, 2005;Morrison and Brickman, 2006). Our results show that this same regulatory module, i.e., the negative cross-regulation between Oct3/4 and Cdx, is employed to regulate the transition into gastrulation.…”
Section: Discussionsupporting
confidence: 76%
“…These results identify Oct3/4 as a factor contributing to the expression of the Cdx genes and actually activating one of the factors involved in its own repression. Several studies have shown that during gastrulation, the Xenopus Oct3/4 factors function in a manner consistent with the active maintenance of the pluripotent state like their mammalian homologues (Henig et al, 1998;Cao et al, 2006Cao et al, , 2007Morrison and Brickman, 2006;Snir et al, 2006). Thus, Cdx1 acting as a negative regulator of the Pou5f1 genes during gastrulation, would ultimately function to end the undifferentiated state and facilitate the transition into gastrulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations